RETRACTED: Methods of scientific foresight in assessing the sustainability of the functioning of enterprises in high-tech industries - Kazmina Irina; Rodionova Valentina; Krasnikova Anna; Shchegoleva Tatiana (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001